Predictors of malnutrition among adolescents in Egypt: a nationwide cross-sectional study - Nehal M. El-Koofy; Marwa Sabry Rizk; Marwa M. Zein; Eman Mohamed Ibraheim Moawad; Sara Tarek (Egyptian Pediatric Association Gazette)
Abstract Background Adolescence is a unique stage of human life characterized by intense physical growth and development. Making poor choices regarding dietary behavior, physical activity, and lifestyle can put adolescents at risk of several diseases. This study aimed to assess the prevalence and predictors of malnutrition among Egyptian adolescents. Methodology A cross-sectional study in which a structured interview questionnaire was administered to 4064 young adolescents aged 10–14 recruited from 11 Egyptian governorates. Data about the participants’ anthropometric parameters, dietary patterns, and lifestyles were collected. Results The overall prevalence of short stature, overweight/obesity, and wasting was 18.4% (95% CI 17.2%, 19.6%), 37.5% (95% CI 36%, 39%), and 4.8% (95% CI 4.2%, 5.5%), respectively. Multinomial logistic regression was performed to predict the risk factors of overweight, wasting, and stunting. Frequent eating of midnight snacks (OR = 1.368, 95% CI 1.081, 1.730), large consumption of chips (OR = 2.052, 95% CI 1.511, 2.788), and extended TV watching (OR = 1.195, 95% CI 1.038, 1.375) are significant risk factors for overweight. Wasting was less likely to occur with regular intake of vegetables (OR = 0.609, 95% CI 0.372, 0.997) and nuts (OR = 0.406, 95% CI 0.185, 0.887). Female adolescents and unemployed status fathers were risk factors associated with stunting (OR = 1.236, 95% CI 1.047, 1.459, and OR = 1.537, 95%CI 1.078, 2.190). Frequent intake of milk and milk products was less likely associated with stunting (OR = 0.682, 95% CI 0.542, 0.855). Conclusion Unhealthy lifestyles such as extended TV viewing and unhealthy diet and snacks are associated with an increased risk of obesity and stunting in Egyptian adolescents.